2018
DOI: 10.1038/s41467-017-02352-z
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of Atg3 and Atg7 mediates inhibition of autophagy

Abstract: Macroautophagy (autophagy) is a crucial cellular stress response for degrading defective macromolecules and organelles, as well as providing bioenergetic intermediates during hypoxia and nutrient deprivation. Here we report a thiol-dependent process that may account for impaired autophagy during aging. This is through direct oxidation of key autophagy-related (Atg) proteins Atg3 and Atg7. When inactive Atg3 and Atg7 are protected from oxidation due to stable covalent interaction with their substrate LC3. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
125
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(132 citation statements)
references
References 48 publications
(64 reference statements)
7
125
0
Order By: Relevance
“…Although both dysfunctions are thought to be causally linked, the respective place of mitochondria and lysosomes in mediating this mechanism is challenging to elucidate in view of the interdependence of these organelles. On the one hand, mitochondria can act upstream of lysosomal dysfunction by generating reactive oxygen species (ROS) that can impair autophagy (7) or by reducing ATP production, which is essential for lysosomal vacuolar ATPase (vATPase)-mediated acidification. On the other hand, accumulation of damaged mitochondria can occur downstream to lysosomal dysfunction within the mitochondrial quality control mechanism, which, as we have previously reported, consists of targeting fragmented depolarized mitochondria to autophagy for degradation (8).…”
mentioning
confidence: 99%
“…Although both dysfunctions are thought to be causally linked, the respective place of mitochondria and lysosomes in mediating this mechanism is challenging to elucidate in view of the interdependence of these organelles. On the one hand, mitochondria can act upstream of lysosomal dysfunction by generating reactive oxygen species (ROS) that can impair autophagy (7) or by reducing ATP production, which is essential for lysosomal vacuolar ATPase (vATPase)-mediated acidification. On the other hand, accumulation of damaged mitochondria can occur downstream to lysosomal dysfunction within the mitochondrial quality control mechanism, which, as we have previously reported, consists of targeting fragmented depolarized mitochondria to autophagy for degradation (8).…”
mentioning
confidence: 99%
“…For instance, a similar situation has been observed in sepsis, in which the rate of autophagic clearance of damaged organelles was outpaced by the extent of sustained insult to hepatocytes . Conversely, it is possible that the increase in oxidative stress impairs autophagic activity in cells …”
Section: Autophagy In the Ageing Heartmentioning
confidence: 69%
“…37 Conversely, it is possible that the increase in oxidative stress impairs autophagic activity in cells. 38,39 Metabolic and hormonal changes accompanying ageing may contribute to lower levels of autophagy. Age-related activation of autophagy suppressors, in addition to inhibition of autophagy activators, may also play a role here.…”
Section: Autophagy In the Ageing Heartmentioning
confidence: 99%
“…Furthermore, direct up-regulation of autophagy has been shown to exert health benefits and extend lifespan in a range of model organisms including worms, flies and mice 3739 . Several components of the autophagy pathway are known to be redox regulated, including Atg3 and Atg7 40 , as well as the focus of our study Atg4 26 . Overall, we have shown that shifting the in vivo redox state of Drosophila through over-expression of catalase extends lifespan and healthspan in females through redox regulation of autophagy via a key redox-regulatory cysteine in Atg4a.…”
Section: Figmentioning
confidence: 99%